ELECTRICAL CONSTRUCTION KITS AND THEIR INFLUENCE ON TEACHING - SERAFIN, Cestmir (Journal of Technology and Information Education, 2012)
The efficiency of the education is variable, which is very difficult to measure, influenced by a variety of input components-students, teachers, school curricula, the school's internal and external factors. Generally, it is necessary to assess the degree of efficiency of the functioning of the training to carry out a comparison of the rate variables describing the inputs with the same intensity of quantities characterizing the outputs. This article deals with the intermediate results of the research evaluating the scope of the efficiency of the functioning of the educational process in the field of education and training of the ``man and the world of work'' in the context of electrical engineering. Research to check whether the electrical construction kits influence on teaching and that their use reflects the results of the pupils. The objects of research were pupils and subject of research is their knowledge and understanding.
Keywords: education; efficiency; electrical construction kits; project training; subject didactics